If it's not what You are looking for type in the equation solver your own equation and let us solve it.
X+9=2X+4X=
We move all terms to the left:
X+9-(2X+4X)=0
We add all the numbers together, and all the variables
X-(+6X)+9=0
We get rid of parentheses
X-6X+9=0
We add all the numbers together, and all the variables
-5X+9=0
We move all terms containing X to the left, all other terms to the right
-5X=-9
X=-9/-5
X=1+4/5
| 42x+1=44 | | 12x-3x+99=12x+48 | | 82+x+45+x+65=180 | | -41=(-9h)+22 | | F(-8)=4x+13 | | 2x-3(x+6)=-4(x+1 | | 3r^2+3r-36=0 | | -15=-1x+27 | | -6(r-1)+26=14 | | p+6=p+9 | | 94=3v+22 | | -5q+8=-10+4q | | 8k+23=95 | | -3(5-2x-6+4x=9 | | 3(4)+y=-1 | | -3/4x+15=3 | | 2y+5=40 | | 5/6b=79.50 | | h+1=6h+1-5h | | 23x=-30 | | -255=3d | | 17x+21+57=180 | | 5x+71=-14 | | {2}{3}x=-30 | | 5.x-70=216-8.x | | 3f-23=10 | | 9m+3=-5 | | −2(−3x+8)=6(x+4)−3 | | 2/3(9x-6)=9 | | -4t=116 | | -4x-7(-3x-6)=135 | | -6(5k+3)=-18-k |